Cover Crops May Cause Winter Warming in Snow‐Covered Regions. Issue 18 (28th September 2018) - Lombardozzi, D. L.; Bonan, G. B.; Wieder, W.; Grandy, A. S.; Morris, C.; Lawrence, D. L.
Abstract: Cover crops, grown between cash crops when soil is fallow, are a management strategy that may help mitigate climate change. The biogeochemical effects of cover crops are well documented, as they provide numerous localized benefits to farmers. We test potential biogeophysical climate impacts of idealized cover crop scenarios by assuming that cover crops are planted offseason in all crop regions throughout North America. Our results suggest that planting cover crops increases wintertime temperature up to 3 °C in central North America by decreasing albedo in regions with variable snowpack. Cover crops with higher leaf area indices increase temperature more by decreasing broadband albedo, while decreasing cover crop height helped to mitigate the temperature increase as the shorter height was more frequently buried by snow. Thus, climate mitigation potential must consider the biogeophysical impacts of planting cover crops, and varietal selection can minimize winter warming. Plain Language Summary: Planting cover crops is an agricultural management technique in which crops are grown in between cash crop seasons when the soil would otherwise be fallow. Cover crops provide many local benefits to farmers and can increase carbon storage in soils. In this study, we test how planting cover crops in all agricultural regions in North America can change wintertime temperatures. Model simulations suggest that cover crops can warm winter temperatures up to 3 °C in regions with variable winter snowpack, such as central North America. Planting cover crop varieties that are less leafy or get buried under the variable snowpack can help to minimize winter warming. Our study suggests that the climate mitigation potential of cover crops may be offset in these regions if cover crop varieties are not carefully selected. Key Points: Cover crops can increase cash crop yields and soil carbon storage and can also induce regional biogeophysical climate impacts Where cover crops extend above winter snowpack, they decrease albedo and warm wintertime temperatures Winter warming can be minimized by planting less leafy cover crops or varieties that will be completely buried under the snowpack